Assessing Road Accident Black Spots and Countermeasures in the State of Perak, Malaysia - Meor Hussein, M M H; Abd Rahman, Raha; Mohd Saim, Nur Amylia Izrin; Megat Tajuddin, Megat Zuhairy; Md Diah, Jezan (International Journal of Sustainable Construction Engineering and Technology, 2023)
To develop a successful strategy for improving road safety, the initial step involves is to identify the black spots that are more susceptible to high-risk traffic accidents. However, due to the high cost of implementing safety measures in these locations, only a limited number of spots/sites can be thoroughly examined with the available funding. Therefore, it is crucial to prioritize the high-risk sites and their corresponding safety measures in order to make the most efficient use of the available finances. Hence, this paper presents black spots ranking and low-cost countermeasures based on the Perak Federal trunk road traffic crash (RTC) data for three years from 2018 to 2020 recorded by the Royal Malaysian Police (RMP). The weightage point method was used for each black spot  ranking exercise where as, the selection for countermeasures were based on RTC situations which are norms practiced by the Public Works Department (PWD). In total 22 black spots were ranked and it was found that the highest rank of the 2020 black spots in Perak was along route FT005 in Kinta district which had 18 RTCs and with a total weightage points (TWP) of 118.2. In balancing between limited financial allocation and improving road safety, the countermeasures were priorotized for implementation in 2021 based on the black spots ranking results. However, only six black spots were treated in 2021 with the entire cost was RM 1,834,027.19.  Where for route FT005 in Kinta district, the countermeasure was done at Section 684 with a total cost of RM350,000 under the 2022 black spots countermeasure program which is an annual program funded by the Ministry of Works Malaysia. It is recommended that Perak State PWD form a Road Safety Unit to reduce the black spots along the state roads which is the second highest road fatalities recorded in Perak.